STUDY CHEMISTRY FOR WHAT? AN INVESTIGATIVE CASE FOR THE DEVELOPMENT OF TEACHER CANDIDATES' ARGUMENTS ABOUT THE IMPORTANCE OF CHEMISTRY IN THE SCHOOL CURRICULUM - Primo, Carolina M. [UNESP]; Ferrarini, Francisco O. C.; Moralles, Vagner A. [UNESP]; Bego, Amadeu M. [UNESP] (Soc Brasileira Quimica, 2025)
The recent secondary curriculum reform in Brazil generated discussions around arguments for the inclusion of specific subjects within the official curriculum. This qualitative study, situated within a teacher education program at a university of S & atilde;o Paulo, investigates the arguments constructed by 31 pre-service teachers concerning the importance of Chemistry in the secondary curriculum. Findings highlight the impact of targeted instructional interventions on challenging pre-existing, naive conceptions held by them. Well-designed interventions foster the development of sophisticated arguments aligned with the value of scientific literacy for secondary students, reflecting deeper understandings of how chemistry education contributes to broader educational goals.
Keywords: school curriculum; investigative case; chemistry education